La formación de la responsabilidad social en la universidad - García Ramos, José Manuel; Calle Maldonado de Guevara, Carmen De La; Giménez Armentia, Pilar (Revista Complutense de Educación, 2007)
Today’s society demands socially committed professionals, therefore, trained in Social Responsibility.The University, faithful to its mission of integrally educating those who attend its classes, has to give an answer to this urgent need of people who consider their professional development within the commitment with others and their environment. This paper is Francisco de Vitoria University’s proposal about this issue, presenting it as an university mandatory course. More than ten years of experience and achievements bases on this pioneer initiative, endorse this bid in favour of the university student’s education in Social Responsibility.